Effects of mind–body exercise on physical ability, mental health and quality of life in stroke patients: a systematic review and meta-analysis - Dong, Jin; Chi, Jinjin; Wang, Desheng (Frontiers in Public Health, 2024)
Purpose To systematically evaluate the effects of mind–body exercise on physical ability, mental health and quality of life in stroke patients. Methods According to the PRISMA statement, we searched Web of science, Pubmed, Embase, Sinomed, CNKI, Wanfang, and VIP databases to collect randomized controlled trials on the effects of mind–body exercise on improving balance function, motor capacity, walking function, depression and quality of life in stroke patients. The search was conducted in January 2024. Review Manager5.3 was used for statistical analysis of the data. Results A total of 33 randomized controlled trials with a total of 1985 participants were included. The results of meta-analysis showed: Mind–body exercise had a significantly effect on balance ability [MD = 5.64, 95%CI = 4.17, 7.11, p < 0.00001], upper limb motor ability [MD = 6.98, 95%CI = 1.96, 12.01, p = 0.006 < 0.01], lower limb exercise capacity [MD = 3.55, 95% CI = 0.31, 6.78, p = 0.03 < 0.05], exercise capacity [MD = 7.24, 95% CI = 4.36, 10.12, p < 0.00001], depression [MD = −3.28, 95%CI = −3.86, −2.69, p < 0.00001] and quality of life [MD = 10.62, 95%CI = 5.17, 16.06, p = 0.0001 < 0.01]. However, mind–body exercise did not affect walking ability [MD = −1.82, 95%CI = −4.20, 0.57, p = 0.14 > 0.05]. The results of subgroup analysis showed: Qigong (Baduanjin) exercise for more than four weeks, 6–10 times a week, 15–40 min each time can significantly improve balance function and quality of life in stroke patients. Conclusion Mind–body exercise can be used as a supplement therapy to conventional rehabilitation therapy, which is not only low intensity, high safety, but also because it is not limited to the site, can be accepted by most people and accelerate the rehabilitation process of stroke.